Implementación del proceso contable en el almacén agropecuario el sembrador de la parroquia Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos; periodo: julio - septiembre del 2013 - Abad Sarango, Piedad Esther (2015)
This research paper entitled: "IMPLEMENTATION OF THE ACCOUNTING PROCESS IN AGRICULTURAL STORE THE NEW PARISH SEMBRADOR Loja, SOUR LAKE CANTON, SUCUMBÍOS Province; PERIOD: JULY - SEPTEMBER 2013, "it ran according to information provided by the business owner, knowing the needs and weaknesses of the same; in order to provide theoretical and practical knowledge that will help the owner to take better control of the economic movements of your business. I was also developed in order to obtain the degree of Engineering in Accounting and Auditing, CPA. The goals set at the beginning of the investigation were met, verified and organized source of business documents, the Plan and User Accounts, inventory of all property, conducting Kardex card formats for control of source documents and worked recording daily economic activities and entire accounting process: Initial Inventory, State Initial Situation, Daybook, majorization, Balance, Worksheet and Financial Statements; thus allowed the owner to know how much was your income, expenses and profits of your business. Once investigative work completed, the owner reported the results of all the movements of its business and it’s also turn recommended to continue applying this process, which will let you know as is economically.